2017
DOI: 10.1186/s41936-017-0011-5
|View full text |Cite
|
Sign up to set email alerts
|

Callyspongia crassa and C. siphonella (Porifera, Callyspongiidae) as a potential source for medical bioactive substances, Aqaba Gulf, Red Sea, Egypt

Abstract: Background: Sponges are champion of bioactive producers because of the variety of products that have been found from them. Most bioactive compounds extracted from sponges were classified into antibiotic, antiviral, antitumor, and anti-inflammatory. Tow marine sponge species were collected during winter 2016 from Gulf of Aqaba, Red Sea, Egypt viz., Callyspongia crassa and Callyspongia siphonella. The collected sponge species belong to family Callyspongiidae. The sponge samples were extracted by ethanol and inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…The detection and quantification of extracted LPS were carried out by the Limulus Amebocyte Lysate (LAL) assay using PYROGENT-5000 kit (Sigma-Aldrich, USA) according to the manufacturer instructions 15 .…”
Section: Extraction Detection and Measurement Of Endotoxin(s)mentioning
confidence: 99%
See 2 more Smart Citations
“…The detection and quantification of extracted LPS were carried out by the Limulus Amebocyte Lysate (LAL) assay using PYROGENT-5000 kit (Sigma-Aldrich, USA) according to the manufacturer instructions 15 .…”
Section: Extraction Detection and Measurement Of Endotoxin(s)mentioning
confidence: 99%
“…Chemical treatment of endotoxin extracted from P. aeruginosa ATCC 9027, either by 1N NaOH, HCl or ethyl alcohol (70% and 100%), resulted in detectable lowering in its activity (44.7%, 68.5%, 64.7% and 88.5%, respectively) after 60 min of treatment as reported by Magalh ‫ד‬es et al 34 . Ibrahim et al 15 examined four NaOH concentrations (0.1, 0.2, 0.5, and 1.0 N) influencing the stability of endotoxin produced by E. coli AS10. They concluded that endotoxin activity and concentration decreased upon the increase of NaOH normality and endotoxin lost about 69% and 81% of its activity/concentration at 0.5 N and 1 N, respectively.…”
Section: Determination Of Endotoxin Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…A biodiversity hotspot, the Red Sea has a high degree of endemism (Dibattista et al, 2016;Osman et al, 2020). Its unique reefs are also a rich potential source of natural products and medicines (Shaala et al, 2015;Ibrahim et al, 2017). The high degree of endemism and adaptation to high salinity and high temperature could potentially have led to the appearance of unique molecules and metabolites not to be found in other reef systems of the world (O'Rourke et al, 2016(O'Rourke et al, , 2018Kremb et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Callyspongia sp. has activity as antibacterial, antifungal, promoting antitumor, antiretroviral, and anti-inflammation [2,3]. Previous studies showed that Callyspongia sp.…”
Section: Introductionmentioning
confidence: 99%